Advances in Hemostatic Wound Dressings: Clinical Implications and Insight. (February 2022) - Agarwal, Roopali; Niezgoda, Jonathan; Niezgoda, Jeffrey; Madetipati, Nethaji; Gopalakrishnan, Sandeep
Abstract : ABSTRACT: Hemorrhagic shock is one of the leading causes of prehospital death in the armed forces. In this state, the body begins to shut down because of blood volume depletion. In both civilian and military trauma, a significant number of hemorrhage deaths occur in the first several hours after injury. Researchers all over the globe are working to develop relatively inexpensive and easy-to-transport products to prevent soldiers from going into hemorrhagic shock. For example, many advances have been made during the last several years toward the development of ideal hemostatic dressings. No current hemostatic agents meet all of the requirements, but the ideal dressing would fulfill many important measures: minimizes or stops blood flow within minutes, contains hemostatic agents to enhance blood clotting, is easy to apply, does not need preapplication preparation, has a reasonably long shelf life, is safe to use, prevents bacterial or viral transmission, is stable at extreme temperatures, and is inexpensive.  For this literature review, the authors conducted an extensive search of academic scientific databases for relevant keywords and assessed and summarized the results. This review aimed to identify recent advances in hemostatic wound dressings; summarize the currently available dressings and their supporting literature; and discuss the compositions, mechanisms of action, and clinical relevance of each category of dressing. In addition, case studies and suggestions for future research into hemorrhage control with new hemostatic agents are provided.